To solve the equation \(2x - 5 = 3(4x + 5)\), here are the ordered steps:
-
Distribute on the right side: \[ 3(4x + 5) = 12x + 15 \] So the equation becomes: \[ 2x - 5 = 12x + 15 \]
-
Subtract \(12x\) from both sides: \[ 2x - 12x - 5 = 15 \] This simplifies to: \[ -10x - 5 = 15 \]
-
Add 5 to both sides: \[ -10x - 5 + 5 = 15 + 5 \] Which simplifies to: \[ -10x = 20 \]
-
Divide both sides by -10: \[ x = \frac{20}{-10} \] Thus: \[ x = -2 \]
-
(Optional) Check your solution: Substitute \(x = -2\) back into the original equation to verify: \[ 2(-2) - 5 \stackrel{?}{=} 3(4(-2) + 5) \] \[ -4 - 5 \stackrel{?}{=} 3(-8 + 5) \] \[ -9 \stackrel{?}{=} 3(-3) \] \[ -9 = -9 \]
Since both sides are equal, the solution \(x = -2\) is confirmed correct.
So the ordered steps to solve the equation are:
- Distribute on the right side.
- Subtract \(12x\) from both sides.
- Add 5 to both sides.
- Divide both sides by -10.
- (Optional) Check your solution.